Synthesis, characterization, electrochemistry and Antimicrobial Activity of Zinc(II) complexes of some hydrazone schiff bases - Ali, Hapipah Mohd; Sharifah Rohaiza, S.O.; Nazri, L.P.M.; Teoh, H.L.; Abdullah, N.; Zain, S.M.; Basirun, Wan Jefrey; Subramaniam, P. (Faculty of Science, University of Malaya, 2006)
A series of hydrazone Schiff bases and their zinc(II) complexes have been synthesized, characterized and evaluated for antimicrobial activity. The new zinc(II) complexes have been prepared in ethanol media by a template condensation of hydrazides, with either ketone or aldehyde and zinc(II) acetate in the presence of triethylamine. The IR, 1H and 13C NMR data indicate that the hydrazone ligands are coordinated to zinc metal. The cyclic voltammetry of these zinc complexes exhibited irreversible oxidation peaks. The electro-oxidation of Zn 2(Clhaptch) 2(py) 2 displayed a diffusion-controlled one electron transfer reaction process. The antimicrobial activity of the ligands and complexes were evaluated by plate diffusion method against some gram-positive bacteria, gram-negative bacteria and two fungi. There was growth inhibition exhibited by ligands and zinc(II) complexes against tested bacteria and fungi.